Political theory & public policy - GOODIN, Robert E ([Tidak Terdaftar], 1982)
Some say that public policy can be made without the benefit of theory—that it emerges, instead, through trial-and-error. Others see genuine philosophical issues in public affairs but try to resolve them through fanciful examples. Both, argues Robert E. Goodin, are wrong.